Cunoniaceae, new family food plant record for the high altitude Andean genera Penaincisalia and Micandra (Lycaenidae: Theclinae: Eumaeini) - Faynel, Christophe (2022)
Caterpillars of two Andean species of Eumaeini (Lycaenidae: Theclinae) were found eating leaves of Weinmannia crassifolia Ruiz & Pav., 1802 (Cunoniaceae). They were collected by “beating” the leaves. This plant family is reported for the first time as a food plant for Eumaeini. Although it was not possible to rear the caterpillars to the adult stage, we identified them using DNA barcodes. The caterpillars of Penaincisalia purpurea (K. Johnson, 1992) and Micandra dignota (Draudt, 1919) are described and illustrated for the first time. Data on their ecology and relationships with similar species are also presented. A third species collected on the same plant of W. crassifolia in the pupal stage was a Nymphalidae, Perisama diotima (Hewitson, 1852).